2015
DOI: 10.1111/dote.12372
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence in situ hybridization identifies high risk Barrett's patients likely to develop esophageal adenocarcinoma

Abstract: SUMMARY Barrett’s esophagus (BE) with high-grade dysplasia (HGD) defines a group of individuals at high risk of progression to esophageal adenocarcinoma (EA). Fluorescence in situ hybridization (FISH) has been shown to be useful for the detection of dysplasia and EA in endoscopic brushing specimens from BE patients. The aim of this study was to determine whether FISH in combination with histological findings would further identify more rapid progressors to EA. This is a retrospective cohort study of high-risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 11 publications
(26 reference statements)
0
12
0
Order By: Relevance
“…Additionally, recent evidence has suggested that FISH may play a role in risk-stratifying individuals with dysplasia. A retrospective analysis of patients with HGD found that if more than 4 of 100 cells had evidence of polysomy, there was a higher likelihood of progression to EA [22]. Although further verification is needed, these findings suggest that genetic changes detected by FISH can both predict HGD lesions elsewhere in the esophageal column as well as progression to EA.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, recent evidence has suggested that FISH may play a role in risk-stratifying individuals with dysplasia. A retrospective analysis of patients with HGD found that if more than 4 of 100 cells had evidence of polysomy, there was a higher likelihood of progression to EA [22]. Although further verification is needed, these findings suggest that genetic changes detected by FISH can both predict HGD lesions elsewhere in the esophageal column as well as progression to EA.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have evaluated FISH probes directed against tumor suppressor and proto-oncogenes, such as 8q24 (c-MYC), 9p21 (p16), 17q11.2 (HER2/neu), 17q13.1 (p53), and 20q13.2 (ZNF217) in various BE populations. 44 FISH assays can be performed by using commercially available kits available through multiple companies and tertiary-care centers. These assays are being used in practice to aid in risk stratification of patients with BE for progression to esophageal cancer.…”
Section: Fluorescence In Situ Hybridizationmentioning
confidence: 99%
“…[46][47][48] The utility of FISH to risk-stratify patients with HGD who will progress to EAC also has been evaluated. 44 In a singlecenter retrospective study, 245 patients with prior biopsyproven HGD without EAC underwent brush cytology during surveillance endoscopy. The authors evaluated the brushing specimens by using the previously described Vysis 4-probe panel for the presence of polysomy; 93 patients (38%) had polysomy detected in at least 1 target gene, and 152 patients (62%) did not.…”
Section: Fluorescence In Situ Hybridizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Stachler study, the number of gene amplifications defined by ploidy > 3 increased to 8.44 per EAC sample compared to 0.42 per non‐dysplastic BE sample [Stachler et al, ]. The usefulness of global measures of aneuploidy and chromosomal changes [Li et al, ; Nones et al, ; Timmer et al, ] and established FISH panels [Brankley et al, ] need to be compared against panels of somatic microRNA gene alterations; this comparison will require collaborative studies to reach the necessary sample sizes.…”
Section: Where Do Tissue and Blood Micrornas Fit Into The Clinical Mamentioning
confidence: 99%